AGE AND COMPOSITION OF THE EARLY PALEOZOIC MAGMATIC ASSOCIATIONS AND RELATED RARE-ELEMENT PEGMATITES IN THE SOUTH-EASTERN PART OF THE SANGILEN BLOCK, TUVA-MONGOLIAN MASSIF - L. G. Kuznetsova; S. P. Shokalsky; S. A. Sergeev; S. I. Dril (Геодинамика и тектонофизика)
The article presents new data on ages (U-Pb zircon dating, SIMS SHRIMP-II) and chemical compositions of rocks from gabbro-granitic and granite-leucogranitic magmatic associations. These rocks preceded the formation of Li-enriched spodumene pegmatites of the Tserigiyngol-Burchin ore cluster (Russian: ЦБРУ), one of the main clusters in the South Sangilen pegmatite belt (SSB) located in the Tuva-Mongolian massif being a part of the Central Asian Fold Belt. We investigated the rocks from the Upper Tserigiyngol, Uchuglyk and Temenchulu plutons, and pegmatites from two neighbouring fields. We distinguish three impulses of granitic magmatism (517±7, 508±7, and 488±6 Ma), which are attributed to different stages of the Early Paleozoic collision orogeny (520-480 Ma). The period when the Li-enriched pegmatites were formed (494±7 Ma) is close to the magmatism impulse at 488±6 Ma. Differences are discovered in compositional and isotopic (Sm-Nd) features of granites dominating at the following stages of collisional orogeny: (1) early collision (517±7 Ma) – I-type granites, eNd(T)=0–1.5, TNd (DM-2st)=1.2–1.1 b.y., and (2) late collision (488±6 Ma) – A-2-type granites, eNd(T)=–3.0…–1.6, TNd (DM-2st)=1.5–1.4 b.y., which are due to different sources. Our study shows that facies transitions are absent between the late-collision granites (488±6 Ma) and the spodumene pegmatites from the Tserigiyngol-Burchin ore cluster (494±7 Ma), although these rocks are close in age. In terms of geochemical features, the spodumene pegmatites from the cluster are strongly different from both the late-collision granites and spodumene pegmatites from other SSB fields, including the large Tastyg lithium deposit. We have analysed the role of interactions between the crustal and mantle materials in the formation of granitoid sources in the Tserigiyngol-Burchin ore cluster, and described their evolution in time and the influence on the pegmatite rare-element specialization.